"Carboranyl-cysteine"—Synthesis, Structure and Self-Assembly Behavior of a Novel α-Amino Acid. Issue 1 (December 2017) - He, Tianyu; Misuraca, Jennifer; Musah, Rabi
Abstract Substitution of the thiol proton in cysteine withm -carborane furnished 2-amino-3-(1, 7-dicarba-closo -dodecacarboranyl-1-thio)propanoic acid (3 ), a boron cluster amino acid that exhibits self-assembly to form micron-sized constructs. Field emission scanning electron microscopy revealed that ethanol solutions of3 form floret-shaped constructs, while fibrillar architectures are formed in water. Furthermore, slow evaporation of methanol solutions of3 produced crystals whose structure was revealed by X-ray crystallography. The crystal structure shows that the hydrogen bonding interactions between pairs of3 result in the formation of bilayers of 174 Å in length. The orientation of the clusters is not random in the crystal structure, such that the side-by-side aligned polyhedra are offset by 158 degrees. The material was characterized by FT-IR, NMR, high resolution mass spectrometry and dynamic light scattering. Circular dichroism studies indicated that self-assembly occurs at concentrations as low as 0.01 μM. This represents the first demonstration of self-assembly of a carborane-based molecule in the absence of metals. The amino acid motif provides opportunities for the controlled synthesis of extended multimeric units with tunable properties and the potential for applications in biology, medicine and materials chemistry.